(untitled) (Research, Society and Development, 2023)
Water temperature is an important physical property for the health of aquatic ecosystems because it affects the concentration of oxygen saturation dissolved in the water and alters chemical and biological reactions that can cause species to have their metabolism, reproduction, growth and survival threatened. Therefore, to ensure that water is compliant for aquaculture production or other area that depend of the temperature, the constant water monitoring is essential. There are several devices that allow this measurement, however, they are not present in all places that have this need. Alternatively, water temperature estimation can be applied in these environments. The objective of this study is to conduct a systematic literature mapping that presents a review of statistical models used to estimate water temperature in rivers. Several statistical models have been used for this purpose in various parts of the world, including Brazil. This mapping aims to identify which models have been used, as well as to perform comparisons and critical analysis of the uses and evaluations of these models.